Screening general population for family history of sudden cardiac death unmasks high risk individuals as potential victims (pilot study) - Lamia Hamid; Alia Abdelfattah; Khaled Hussien; Khaled Farouk; Mohamed Amin; Lina Omar; M. Sherif Mokhtar (Egyptian Journal of Critical Care Medicine)
Abstract As there are no large scale Egyptian surveys estimating the prevalence of cardiac disease and the incidence of SCD in a non-selected population, the purpose of this report was to assess the relation between family history of SCD and the presence of CAD or coronary risk factors in first degree relatives of SCD victims searching for potential victims. A questionnaire screening CAD risk factors and cardiac problems as indicators for SCD was developed, Data were collected from 8786 candidates by means of a questionnaire only protocol (random samples (8117)) and questionnaire plus clinical examination, ECG and laboratory investigations during medical convoys (random samples (669)). Data were coded and verified according to presence and absence of CAD risk factors, IHD and other risk factors in order that a triage could be performed in the general population to detect adults at risk of SCD. Family history of CAD, DM and HTN head the list of risk factors more frequently associated with family history of SCD clearly pointing the role played by those comorbidities in pointing to potential victims of SCD. Compared to those with no family history of SCD, those with positive family history of SCD were 8.7 times more associated with family history of DM, 12 times more associated with family history of CAD, 7 times more associated with family history of HTN. This study underscores the importance of searching for positive family history of sudden cardiac death as a warning marker a red flag that makes familial evaluation strongly recommended.